Changes in International Students' Dietary Habits, Physical Activity and BMI During Their First Year After Relocating to the U.S. (7th June 2021) - Rabeeah, Zainab; Shaikh, Nida; Cunningham, Solveig
Abstract: Objectives: To identify changes in diet, physical activity and BMI after 3–6 months of relocation among international students in Georgia, USA. Methods: Data were collected from 74 international students attending 2 urban universities in the Southeast. Students were interviewed within 10 days of arrival in the U.S and again 3–6 months later. Participants completed an interviewer-administered questionnaire that included a 26-item food frequency questionnaire, and questions on weekly physical activity, daily screen-time usage, sleep duration, and anthropometric measurements (body weight, height, and waist circumference), each measured twice and then averaged. Student t-test, Chi square and ANOVA analysis was done for participants who completed both waves (n = 74). Results: Participants reported consistent food consumption within 3–6 months (mean difference < 0.5 times per week). Physical activity frequency remained consistent (mean difference < 0.5), but duration of almost all activities was increased. Participants reported increased hiking frequency and a significant increase in duration (frequency mean 0.05 to 0.09 times/week, 95% CI of (0.02–0.08) to (0.02–0.16), duration mean 21.1 to 117 minutes/week, 95% CI (14.1–28.0) to (94.7–138.5)). Screen time significantly increased (mean 4.2 to 7.0 hours/day, 95% CI (3.6–4.9) to (6.2–7.8)). Mean weight slightly increased (62.7 kg to 62.9 kg, 95% CI (60.5–65.0)), as did mean BMI (22.4 to 22.6, 95% CI (21.6–23.2)). However, around 37% of participants gained > 10% of their baseline weight, while 32% lost > 10% of their baseline weight. Almost half of participants (44.5%) reported that they had gained weight and 77% reported a decrease in their overall health. Conclusions: Follow-up data suggests International students' body weights changed drastically in a short time period which could potentially lead to negative health outcomes. Funding Sources: None.